PKM2 Is the Target of a Multi-Herb-Combined Decoction During the Inhibition of Gastric Cancer Progression - Sun, Qingmin; Yuan, Mengyun; Wang, Hongxing; Zhang, Xingxing; Zhang, Ruijuan; Wang, Haidan; Chen, Xu; Zhu, Min; Liu, Shenlin; Wu, Jian (Frontiers in Oncology, 2021)
Gastric cancer is still the most commonly diagnosed cancer in worldwide. Traditional Chinese medicine (TCM) is increasingly extensively applied as a complementary therapy for gastric cancer (GC) in China, which shows unique advantages in preventing gastric cancer metastasis. Previous study indicates modified Jian-pi-yang-zheng (mJPYZ) decoction inhibit the progression of gastric cancer by regulating tumor-associated macrophages (TAM). However, it is unclear whether mJPYZ can affect metabolic reprogramming of gastric cancer cells. Here, we showed that mJPYZ effectively attenuated GC cells proliferation, migration and invasion. Meantime, mJPYZ reduced the aerobic glycolysis level of GC cells in vivo and in vitro by regulating the expression and nuclear translocation of PKM2. PKM2 reversed the inhibitory effect of mJPYZ on GC cells proliferation, migration and epithelial to mesenchymal transition (EMT). Our results showed PKM2/HIF-1α signaling was the key metabolic regulator of mJPYZ in GC cells. In summary, our present study suggested that abnormal PKM2 is required for maintaining the malignant phenotype of GC cells. The TCM decoction mJPYZ inhibited GC cells growth and EMT by reducing of glycolysis in PKM2 dependent manner. This evidence expanded our understanding of the anti-tumor mechanism of mJPYZ and further indicated mJPYZ a potential anti-tumor agent for GC patients.